Moderation Islamic Spiritual Values in Social Entrepreneurship Learning Models - Nugroho, Arif Julianto Sri; Marjukah, Anis; Haris, Abdul; Jati, Agung Nugroho; Santoso, Gunawan Budi (Letiges, 2024)
This research tests the dependent variable of business longevity among social micro-business actors, influenced by three independent variables: attitudinal values, self-efficacy, and cognitive dissonance, with the moderating variable of Islamic spiritual values. The goal is to develop a social entrepreneurship learning model for students based on local wisdom and values. The research model modifies the theory of planned behavior by enhancing the attitude concept and adding moderating variables, including Islamic spiritual values. Quantitative survey research employing purposive sampling was conducted with 200 adult Muslim social micro-business actors in the Klaten area. Structural Equation Model tests reveal direct influences of attitude values, self-efficacy, and cognitive dissonance on business longevity. The moderation test for Islamic spiritual values strengthens attitude and self-efficacy while weakening cognitive dissonance. Managerial implications suggest strategies to enhance the Islamic spiritual value ethos. Future sustainable activities include developing learning model textbooks for students based on local wisdom values to reinforce attitude values and self-efficacy and mitigate cognitive dissonance concerning business sustainability. The findings indicate a moderate level of religiosity in the Klaten Regency area, hindering the moderating role of Islamic spiritual values.